The Evaluation of the North Atlantic Climate System in UKESM1 Historical Simulations for CMIP6. (15th September 2020) - Robson, Jon; Aksenov, Yevgeny; Bracegirdle, Thomas J.; Dimdore‐Miles, Oscar; Griffiths, Paul T.; Grosvenor, Daniel P.; Hodson, Daniel L. R.; Keeble, James; MacIntosh, Claire; Megann, Alex; Osprey, Scott; Povey, Adam C.; et al.
Abstract: Earth system models enable a broad range of climate interactions that physical climate models are unable to simulate. However, the extent to which adding Earth system components changes or improves the simulation of the physical climate is not well understood. Here we present a broad multivariate evaluation of the North Atlantic climate system in historical simulations of the UK Earth System Model (UKESM1) performed for CMIP6. In particular, we focus on the mean state and the decadal time scale evolution of important variables that span the North Atlantic climate system. In general, UKESM1 performs well and realistically simulates many aspects of the North Atlantic climate system. Like the physical version of the model, we find that changes in external forcing, and particularly aerosol forcing, are an important driver of multidecadal change in UKESM1, especially for Atlantic Multidecadal Variability and the Atlantic Meridional Overturning Circulation. However, many of the shortcomings identified are similar to common biases found in physical climate models, including the physical climate model that underpins UKESM1. For example, the summer jet is too weak and too far poleward; decadal variability in the winter jet is underestimated; intraseasonal stratospheric polar vortex variability is poorly represented; and Arctic sea ice is too thick. Forced shortwave changes may be also too strong in UKESM1, which, given the important role of historical aerosol forcing in shaping the evolution of the North Atlantic in UKESM1, motivates further investigation. Therefore, physical model development, alongside Earth system development, remains crucial in order to improve climate simulations. Plain Language Summary: The North Atlantic climate system plays an important role in regulating Earth's climate, and variability within the Atlantic can have important impacts on society. However, we do not understand all the linkages between different parts of the North Atlantic. Furthermore, climate simulations, which are an essential tool for improving our understanding, have shortcomings that can affect their utility. New developments in Earth System climate simulations could remedy these shortcomings. However, we do not understand the extent to which the addition of complex Earth system developments have changed or improved the simulation of the physical climate. Therefore, in this paper, we present a multidisciplinary evaluation of the North Atlantic climate in simulations made with the UK's Earth System Model, UKESM1. We find that simulations made with UKESM1 capture many aspects of the North Atlantic climate and that human activities have a large impact on the North Atlantic in UKESM1. Nevertheless, we also highlight some shortcomings of the simulations, many of which are like those seen in physical climate simulations. Therefore, further development of both the physical and Earth system components is needed to improve climate simulations in the future. Key Points: UKESM1 performs well across a range of variables and components of the North Atlantic climate system when compared with observations A range of shortcomings are still present in the simulations, however, with many shortcomings similar to those of the physical climate model Development of the physical model, alongside the Earth system components, is crucial for improved climate simulations